2011
DOI: 10.1111/j.1399-0012.2011.01432.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐cryopreserved hematopoietic stem cell transplantation in multiple myeloma, a single center experience

Abstract: Several clinical trials have shown the superiority of high-dose therapy (HDT) and autologous stem cell transplantation (ASCT) over conventional dose therapy for patients with multiple myeloma. There is limited experience with non-cryopreserved autologous hematopoietic stem cell transplantation. Between January 2004 and February 2010, we treated 38 patients with myeloma (mean age = 50.6) with a preparative regimen of Melphalan 140-200 mg/m(2) and non-cryopreserved ASCT. All the apheresis products were kept in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…Several reports have described the feasibility of noncryopreserved G-CSF-mobilized whole blood or autologous bone marrow (with or without previous administration of G-CSF). Stem cell graft containing blood units or bone marrow can be stored briefly in a standard blood bank refrigerator at +4°C until infusion [28][29][30].…”
Section: Performing Autologous Hsct Without Stem Cell Cryopreservationmentioning
confidence: 99%
“…Several reports have described the feasibility of noncryopreserved G-CSF-mobilized whole blood or autologous bone marrow (with or without previous administration of G-CSF). Stem cell graft containing blood units or bone marrow can be stored briefly in a standard blood bank refrigerator at +4°C until infusion [28][29][30].…”
Section: Performing Autologous Hsct Without Stem Cell Cryopreservationmentioning
confidence: 99%
“…Subsequent in vitro and clinical studies on humans showed that bone marrow cells can be preserved in liquid state for 2 to 9 days without significant loss of granulocyte/macrophage-committed progenitor cells providing hematologic reconstitution to patients receiving myeloablative therapy [56]. The technique may be of value in 2 scenarios: (1) use in medical institutions from areas with limited economic resources, that is, having infrastructure to treat hematologic malignancies but not cryopreservation facilities and (2) use in medical institutions treating hematologic malignancies and in the process of establishing an HSCT program that will eventually have cryopreservation capabilities [5659]. …”
Section: Autologous Transplantation Without Cryopreservationmentioning
confidence: 99%
“…Stem cell transfusion 8 to 24 hours following IV administration of melphalan has been reported to be associated with successful grafts. The dose of melphalan can range between 140 and 220 mg/m 2 [56, 59]. In a systemic review of the published studies on noncryopreserved autologous PBSCT in a variety of malignant hematological disorders including MM, the following results were obtained: (1) median time to neutrophil recovery ranged between 9 and 14 days, (2) median time to platelet recovery ranged between 13.5 and 25 days, and (3) hematopoietic reconstitution was universal in all the studies that included 560 patients.…”
Section: Autologous Transplantation Without Cryopreservationmentioning
confidence: 99%
See 1 more Smart Citation
“…To Editor, We read with interest the report on the use of noncryopreserved stem cells in myeloma. (1). We have recently started our stem cell transplantation program and would like to share the successful outcome with conventional storage of stem cells despite having state-of-the-art cryopreservation facility.…”
mentioning
confidence: 99%